Association between self-reported functional capacity and major adverse cardiac events in patients at elevated risk undergoing noncardiac surgery: a prospective diagnostic cohort study. (January 2021) - Lurati Buse, Giovanna A.L.; Puelacher, Christian; Gualandro, Danielle Menosi; Genini, Alessandro S.; Hidvegi, Reka; Bolliger, Daniel; Arslani, Ketina; Steiner, Luzius A.; Kindler, Christoph; Mueller, Christian; ,; Gueckel, Johanna; et al.
Abstract: Background: Perioperative cardiovascular guidelines endorse functional capacity estimation, based on 'cut-off' daily activities for risk assessment and climbing two flights of stairs to approximate 4 metabolic equivalents. We assessed the association between self-reported functional capacity and postoperative cardiac events. Methods: Consecutive patients at elevated cardiovascular risk undergoing in-patient noncardiac surgery were included in this predefined secondary analysis. Self-reported ability to walk up two flights of stairs was extracted from electronic charts. The primary endpoint was a composite of cardiac death and cardiac events at 30 days. Secondary endpoints included the same composite at 1 yr, all-cause mortality, and myocardial injury. Results: Among the 4560 patients, mean (standard deviation) age 73 (SD 8 yr) yr, classified as American Society of Anesthesiologists physical status ≥3 in 61% ( n =2786/4560), the 30-day and 1-yr incidences of major adverse cardiac events were 5.7% (258/4560) and 11.2% (509/4560), respectively. Functional capacity less than two flights of stairs was associated with the 30-day composite endpoint (adjusted hazard ratio 1.63, 95% confidence interval [CI] 1.23–2.15) and all other endpoints. The addition of functional capacity information to the revised cardiac risk index (RCRI) significantly improved risk classification (functional capacity plus RCRI vs RCRI: net reclassification improvement [NRI]Events 6.2 [95% CI 3.6–9.9], NRINonevents 19.2 [95% CI 18.1–20.0]). Conclusions: In patients at high cardiovascular risk undergoing noncardiac surgery, self-reported functional capacity less than two flights of stairs was independently associated with major adverse cardiac events and all-cause mortality at 30 days and 1 yr. The addition of self-reported functional capacity to surgical and clinical risk improved risk classification. Clinical trial registration: INCT 02573532.